1983
DOI: 10.1007/bf00250156
|View full text |Cite
|
Sign up to set email alerts
|

Sexual responsiveness in diabetic women

Abstract: Summary. Sexual responsiveness in 82 Type 1 (insulin-dependent) diabetic women was compared with that of 47 normal control subjects, using an interview method for rating various aspects of sexual response, and attitude questionnaires. The diabetic women were questioned about symptoms of autonomic neuropathy, and cardiovascular autonomic nerve function tests were performed. There were differences between the two groups in the reports of vaginal lubrication, but in most other respects the groups were similar. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
1
2

Year Published

1985
1985
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 11 publications
3
47
1
2
Order By: Relevance
“…In the present study, decreased sexual desire was reported by 17% of the women with diabetes and 9% of the control women. These numbers are concordant with previous studies with prevalence rates varying between 11 and 45% in diabetic women and between 10 and 31% in control subjects (21,22,26,27). Reduced vaginal lubrication was reported by 14% of women with diabetes and 6% of the control women in our study.…”
Section: Enzlin and Associatessupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, decreased sexual desire was reported by 17% of the women with diabetes and 9% of the control women. These numbers are concordant with previous studies with prevalence rates varying between 11 and 45% in diabetic women and between 10 and 31% in control subjects (21,22,26,27). Reduced vaginal lubrication was reported by 14% of women with diabetes and 6% of the control women in our study.…”
Section: Enzlin and Associatessupporting
confidence: 93%
“…Reduced vaginal lubrication was reported by 14% of women with diabetes and 6% of the control women in our study. Prevalence rates found in the literature vary between 10 and 34% of the women with diabetes and between 5 and 24% of the control women (21,22,26,27). Only Tyrer's and our study showed a significant difference between diabetic and control women.…”
Section: Enzlin and Associatescontrasting
confidence: 63%
“…Our general conclusion is that the noted differences were small and unlikely to have had an important impact on the total HRQOL results. Diabetes is accompanied by complications of different kinds, not only through the traditional diabetic and atheromatous complications, but also through impact on the musculoskeletal system, sexual function, and emotional life (17)(18)(19)(20)(21). Our findings, which showed a major impact on all physical and emotional HRQOL scales in the diabetic patients, are thus logical.…”
Section: Resultsmentioning
confidence: 99%
“…In case of female, diabetic symptoms consistent with autonomic neuropathy associated with decreased subjective sexual arousal. 3) In recent study Erol et al noted that women with type 2 diabetes experienced higher prevalence rates of sexual dysfunction when compared to non diabetic. 4) Approximately 80% of diabetic patients complained loss of libido, 60% had diminished clitoral sensitivity, 50% experienced organic dysfunction, 40% experienced vaginal discomfort, and 40% experienced vaginal dryness.…”
mentioning
confidence: 99%